Pendampingan Parenting Dalam Pemenuhan Gizi Anak Baduta Untuk Pencegahan Stunting - Siti Maryati; Budi Punjastuti; Sumarti Endah Purnamaningsih Maria Margaretha (NERSMID : Jurnal Keperawatan dan Kebidanan, 2021)
Kayuhan Wetan Village Triwidadi Pajangan Bantul which in 2019 was designated as one of the 10 special locations of Stunting Village in Bantul. Partner problems based on stunting data in Puskesmas Pajangan Bantul in 2019 obtained data: 1) Malnutrition as many as 78 children (12.7%), Malnutrition 6 children (0.98%), Number of short toddlers 82 children (13.5%), very short 25 children (4.1%).  2) The level of parental knowledge (Parenting) and parenting practices regarding the nutrition of toddlers in Kayuhan Wetan Hamlet are still lacking. Stunting is caused by multidimensional factors so the handler needs to be done by a multisector. Method mentoring activities to Parenting for The Fulfillment of Child Nutrition BADUTA by providing theoretical and practical training online and offline, as well as conducting assistance in Infant and Child Feeding (PMBA) and Monitoring of child growth. There is an increase in the ability of parenting knowledge in recognizing symptoms and signs of stunting through monitoring the growth and development of children, the most improvement in the component of MP-ASI Knowledge by 4.86 2) There is an increase in parenting skills in the recommended breastfeeding practices in clown children, 3) There is an improvement in parenting skills in Infant and Child Feeding (PMBA) in accordance with the age level (age 6-9 months , 9-12 months and 12-24 months) is appropriate to prevent stunting. Parenting Assistance in Child Nutrition Fulfillment BADUTA is very useful to increase the role of parents (parenting) in order to handle and prevent stunting.